The house ("propriété") of Paul and Laura Lafargue. Original in possesion of Frédéric Longuet. On the right: Jenny Longuet, daughter of Charles, granddaughter of Marx - Dravail, ..., (1902)
The house ("propriété") of Paul and Laura Lafargue. Original in possesion of Frédéric Longuet. On the right: Jenny Longuet, daughter of Charles, granddaughter of Marx.